2004
DOI: 10.1081/jdi-200037117
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Vascular Access Thrombosis in a Cohort of End‐Stage Renal Disease Patients

Abstract: While some studies have demonstrated a relationship between tHcy and VAT, this study found that chronically high homocysteine levels in patients with ESRD were not associated with incidence of VAT. There were no significant differences in the number of VATs across additional variables of age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…Furthermore, no patient entered in the study had patency problems, in this way we tried to minimize the mechanical effects leading to VA thrombosis. Although thrombosis risk and plasma levels of homocysteine are greater in men than female [17][18][19], but we failed to show this association in our study.…”
Section: /4contrasting
confidence: 54%
“…Furthermore, no patient entered in the study had patency problems, in this way we tried to minimize the mechanical effects leading to VA thrombosis. Although thrombosis risk and plasma levels of homocysteine are greater in men than female [17][18][19], but we failed to show this association in our study.…”
Section: /4contrasting
confidence: 54%
“…Paradoxically, two recent studies showed that patients with very low homocysteine plasma levels had worse outcomes including a higher incidence of hospitalization and mortality [7, 8]. This raises the question as to whether elevated homocysteine in uremic patients is consequential rather than causal in the role of cardiovascular complications [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Conclusions from studies examining role of this phenomenon in the context of arteriovenous fistula function are contradictory. Shemin et al (56) and Mallamaci et al (57) believe that the risk of dialysis access thrombosis is high er among patients with high serum homocysteine, while studies by Levesque et al (58) and Bowden et al (59) do not support such relationship.…”
Section: Discussionmentioning
confidence: 72%